Merits of trabeculectomy in advanced and end stage glaucoma - Sofi, Rayees Ahmad; Shafi, Shahnawaz; Qureshi, Waseem; Ashraf, Sehrish (International Journal of Health Sciences, 2018)
Objectives: The aim of the study was to evaluate intraocular pressure (IOP) control, potential benefits and associated complications in advanced cases of glaucoma (visual acuity of less than 6/60) after trabeculectomy. Though many studies of trabeculectomy in glaucoma patients have been done, but very few in such advanced cases. Methods: The study was done on 60 cases of advanced primary open angle glaucoma. Trabeculectomy was done and IOP control was assessed. Preoperative workup included a detailed history, slit lamp biomicroscopy, Goldmann applanation tonometry, gonioscopy using Goldmann 2 mirror lens and detailed fundus examination with the 78D lens. All the patients were to undergo optical coherence tomography and Humphrey automated perimetry. Results: Out of 60 patients with primary open angle glaucoma, 48 were males and 12 were females with a ratio of 4:1. Of all the sixty cases, thirty-six had a visual acuity of 20/200, sixteen had a visual acuity of hand movements (HM), and eight patients had a visual acuity of perception of light (PL). The mean preoperative IOP was measured as 37.01mmHg with SD± 8.82. The mean postoperative IOP was found 17.92mmHg with SD± 3.17. There was a mean drop of 19mmHg of IOP post operatively. The P Value was highly significant (p<0.000). Conclusion: Trabeculectomy is a successful method of controlling intraocular pressure in patients with advanced glaucoma. Trabeculectomy is the method of reducing Intraocular pressure in medically uncontrolled patients. A pain-free eye was associated with better quality of life in patients. A successful trabeculectomy helps to preserve the residual vision in such patients.